Community structure, biomass, and tree species composition across soil and fire gradients in a threatened Amazonian savanna - Vanessa Sousa Gomes; Viviane Vasconcelos Corrêa Dourado; José Júlio Toledo; Albertina Pimentel Lima; Rodrigo Ferreira Fadini (Plant Ecology, 2025)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Conservation opportunities for rare and endemic tropical mistletoes - Rodrigo F. Fadini; Claudenir S. Caires; Greta A. Dettke; Marcelo O.T. Menezes; Francisco E. Fontúrbel (Flora, 2024)

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Responses of ground-dwelling birds and mammals to local environmental variables and human pressure in an Amazonian protected area - Carlos R. Brocardo; Dian C. P. Rosa; Arlison B. Castro; Clarissa Rosa; Kelly Torralvo; Pedro Pequeno; William E. Magnusson; Rodrigo F. Fadini (European Journal of Wildlife Research, 2023)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Bat and bee pollination in Psittacanthus mistletoes, a genus regarded as exclusively hummingbird‐pollinated - Rodrigo F. Fadini; Erich Fischer; Sônia J. Castro; Andréa C. Araujo; Juan Francisco Ornelas; Paulo R. de Souza (Ecology, 2018)

Reaching the canopy on the ground: incidence of infection and host-use by mistletoes (Loranthaceae and Viscaceae) on trees felled for timber in Amazonian rainforests - Jéssica Lira; Claudenir S. Caires; Rodrigo F. Fadini (Plant Ecology, 2017)

A Critical Comparison of Different Approaches to Sediment-Quality Assessments in the Santos Estuarine System in Brazil - Ronaldo J. Torres; Augusto Cesar; Victor A. Pastor; Camilo D. S. Pereira; Rodrigo B. Choueri; Fernando S. Cortez; Rodofley D. Morais; Denis M. S. Abessa; Marcos R. L. do Nascimento; Cassia R. Morais; Pedro S. Fadini; Tomas A. Del Valls Casillas; et al. (Archives of Environmental Contamination and Toxicology, 2015)